Geospatial Thinking - Painho, Marco; Santos, Maribel Yasmina; Pundt, Hardy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book comprises innovative research presented at the conference of the Association of Geographic Information Laboratories for Europe (AGILE), held in May 2010 in Guimaraes (Portugal). The scientifc papers cover a variety of research topics such as geospatial modelling and analysis, quality and semantics of geoinformation, spatial data infrastructures, and spatial decision support systems.
Intersection of Nonconvex Polygons Using the Alternate Hierarchical Decomposition -- Visual Analytics of Urban Environments using High-Resolution Geographic Data -- A Visual Query Language for Spatial Data Warehouses -- The Impact of Data Quality in the Context of Pedestrian Movement Analysis -- Visit Potential: A Common Vocabulary for the Analysis of Entity-Location Interactions in Mobility Applications -- Pre-School Facilities and Catchment Area Profiling: a Planning Support Method -- A Geo-business Classification for London -- Suggestive Geo-Tagging Assistance for Geo-Collaboration Tools -- A Novel Approach to Mining Travel Sequences Using Collections of Geotagged Photos -- Exposing CSW Catalogues as Linked Data -- Applying Semantic Linkage in the Geospatial Web -- A Machine Learning Approach for Resolving Place References in Text -- Towards a Spatial Semantics to Analyze the Visual Dynamics of the Pedestrian Mobility in the Urban Fabric -- Managing Collapsed Surfaces in Spatial Constraints Validation -- A Spatio-Temporal Model Towards Ad-Hoc Collaborative Decision-Making -- iNav: An Indoor Navigation Model Supporting Length-Dependent Optimal Routing -- MIMEXT: a KML Extension for Georeferencing and Easy Share MIME Type Resources -- Schema Mapping in INSPIRE - Extensible Components for Translating Geospatial Data -- Automated Image-Based Abstraction of Aerial Images -- Geospatial Annotations for 3D Environments and their WFS-based Implementation -- Towards Spatial Data Infrastructures in the Clouds.
Keywords: Geography; Mathematical geography; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Computer Applications in Earth Sciences